2004
DOI: 10.1590/s0037-86822004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis of the central nervous system: with report of two cases

Abstract: Clinical involvement of the nervous system in visceral larva migrans due to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 34 publications
1
49
0
10
Order By: Relevance
“…When associated with eosinophilia in the cerebrospinal fluid (CSF), such images are consistent with infection by Toxocara. Observation of larvae of the ascarid in the CSF, in brain tissue or meninges and/or a positive titer for anti-Toxocara antibodies in this fluid represents a decisive diagnosis 72 . In Espirito Santo, Brazil, MUSSO et al 74 examined CSF of children using ELISA IgG anti-Toxocara in order to determine whether any association existed between Toxocara and viral or bacterial infection in the CNS of the same and concluded that infection with this parasite is not associated with viral or bacterial meningitis or meningoencephalitis.…”
Section: Immunoblottingmentioning
confidence: 99%
“…When associated with eosinophilia in the cerebrospinal fluid (CSF), such images are consistent with infection by Toxocara. Observation of larvae of the ascarid in the CSF, in brain tissue or meninges and/or a positive titer for anti-Toxocara antibodies in this fluid represents a decisive diagnosis 72 . In Espirito Santo, Brazil, MUSSO et al 74 examined CSF of children using ELISA IgG anti-Toxocara in order to determine whether any association existed between Toxocara and viral or bacterial infection in the CNS of the same and concluded that infection with this parasite is not associated with viral or bacterial meningitis or meningoencephalitis.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Eosinophilic meningoencephalitis caused by T. canis has been reported in two children who had history of contact with puppy faeces (Moreira-Silva et al 2004), while B. procyonis was also reported in children who had contact with raccoon faecal matter (Chun et al 2009, Page et al 2009). In a literature review, there are a very limited number of cases in which these two parasites caused only eosinophilic meningitis.…”
Section: Resultsmentioning
confidence: 99%
“…Either the patient developed LMND as a consequence of the infection with T. canis or neurotoxocariasis and LMND were causally unrelated and occurred coincidentally in a time-related manner. Arguments for a causal relation are that myelitis and polyradiculitis have been reported as manifestations of an infection with T. canis [2][3][4][5][6][7][8][9][10][11][12][13][14] , that there are human and animal studies indicating that larvae of T. canis also migrate to the spinal cord 9,15 , that antibodies against T. canis persisted in the CSF during clinical deterioration, and that neurotoxocariasis and neurotoxocariasis mimicking motor neuron disease -J. Finsterer et al LMND were time-related. Arguments against a causal relation are that serial MRIs did not show swelling, enhancing structures, or granuloma in the spinal cord or surrounding meningeas, that the patient did not develop upper motor neuron signs, as has been previously reported 10 ; that there was no eosinophilia, neither in the serum nor CSF, although acute myelitis could have passed already and LMND and antibodies against T. canis in the CSF may have been the only remains of the disease, and that albendazole did not resolve the clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Blood investigations may show leukocytosis, eosinophilia, or antibodies against T. canis 9-11 . CSF-investigations may reveal pleocytosis with a high percentage of eosinophils, elevated protein, increased IgG-synthesis, and T. canis antibodies [9][10][11] . On MRI myelitis usually manifests as swelling of the spinal cord with or without enhancement but without compression 10,12,13 Additionally, there may be T2-hyperintensities, preferentially in the posterior and lateral columns 5,10,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation